Impact of Serum Phosphate in Mechanically Ventilated Patients With Severe Sepsis and Septic Shock. (May 2020) - Miller, Christopher J.; Doepker, Bruce A.; Springer, Andrew N.; Exline, Matthew C.; Phillips, Gary; Murphy, Claire V.
Background: Hypo- and hyperphosphatemia are common in severe sepsis and septic shock. Published outcome data in patients with phosphate derangements primarily focus on hypophosphatemia and the general critically ill population. This study aimed to determine the impact of serum phosphate on clinical outcomes in patients with severe sepsis and septic shock. Methods: A retrospective cohort analysis of adult mechanically ventilated patients with severe sepsis or septic shock was performed. Patients were randomly selected from an internal intensive care unit (ICU) database at an academic medical center in the United States and screened for inclusion and exclusion criteria. Time-weighted phosphate was calculated using all phosphate measurements obtained during ICU admission. The associations between time-weighted phosphate and duration of mechanical ventilation, 28-day mortality, and ICU and hospital length of stay were evaluated using linear or logistic regression as appropriate. Results: One-hundred ninety-seven patients were evaluated: 33 were categorized as hypophosphatemia, 123 as normophosphatemia, and 41 as hyperphosphatemia. Patients with time-weighted hyperphosphatemia had a higher Simplified Acute Physiology Score III score and incidence of septic shock. Significantly higher rates of 28-day mortality were observed among those with time-weighted phosphate levels above 3.5 mg/dL. However, both time-weighted hypo- and hyperphosphatemia were associated with decreased duration of mechanical ventilation. For every 0.5 mg/dL increase in time-weighted phosphate referent values from 4.0 to 6.0, the duration of mechanical ventilation decreased by 8% to 26%. For every 0.5 mg/dL decrease in time-weighted phosphate referent values from 3.0 to 1.0, significant decreases in duration of mechanical ventilation ranged from 14% to 41%. Conclusion: Time-weighted hyperphosphatemia may be associated with increased mortality in mechanically ventilated patients with severe sepsis or septic shock. However, time-weighted hypo- and hyperphosphatemia were associated with decreased duration of mechanical ventilation. Future studies should further describe the impact of hypo- and hyperphosphatemia on clinical outcomes among critically ill patients with severe sepsis or septic shock.